2004
DOI: 10.1007/s00181-003-0162-8
|View full text |Cite
|
Sign up to set email alerts
|

Testing J-curve hypothesis and analysing the effect of exchange rate volatility on the balance of trade in India

Abstract: This study estimates the balance of trade model similar to Rose (1991) to test the J-curve hypothesis and analyse the effect of conditional exchange rate volatility on the balance of trade in India. The model is estimated on quarterly data from 1975:02 to 1996:03 and the exchange rate is measured alternatively in terms of the trade and export weighted real effective exchange rate. The model variables are tied together in a long run equilibrium relationship. The study does not find any evidence for the presence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 31 publications
1
20
1
Order By: Relevance
“…And finally, a value below the lower critical value suggests that the variables are not cointegrated. The short-run coefficient at the aggregate level is −1.28 (Table 5.2), which is in line with that obtained by Singh (2004). 16 The long-run coefficient is also negative (−2.88).…”
Section: Aggregate and Bilateral Tradesupporting
confidence: 88%
See 1 more Smart Citation
“…And finally, a value below the lower critical value suggests that the variables are not cointegrated. The short-run coefficient at the aggregate level is −1.28 (Table 5.2), which is in line with that obtained by Singh (2004). 16 The long-run coefficient is also negative (−2.88).…”
Section: Aggregate and Bilateral Tradesupporting
confidence: 88%
“…In a study using the cointegration and ECMs, Rose (1990) finds that there is no strong relation between the REER and the trade balance using three-stage least squares regression on the annual and quarterly data for 30 developing countries including India for the period 1970-88. Similarly, Singh (2004) does not find the presence of a J-curve in the relation between the exchange rate devaluation (using both trade-based and export-based REER) and trade balance for India in his analysis of quarterly data from 1972q2 to 1996q3 using an ECM. The innovation in his study is the use of the GARCH model for the estimates of the REER.…”
Section: J-curve Effects For Indiamentioning
confidence: 89%
“…Narayan (2004) used cointegration method to examine the response of trade balance to currency depreciation in New Zealand and found that the trade balance worsened for the first three years and improved thereafter, indicating the J-curve pattern. However, Singh (2004) did not find similar result for India. He estimated the balance of trade model to test the J-curve hypothesis and analysed the effect of exchange rate volatility on the balance of trade in India for quarterly data from 1975 to 1996.…”
Section: Review Of Literaturecontrasting
confidence: 35%
“…4% of GDP during 20014% of GDP during -20024% of GDP during to 20034% of GDP during -2004. The external position again started deteriorating since the mid-2000s in that the CADs, as a percentage of GDP, progressively rose from 1% in 2006-2007 to 1.3% in 2007-2008, 2.3% in 2008-2009 and 2.8% in 2009-2010. Several studies have examined the CADs and external position in India in the wider context of macroeconomic assessment of the economy Little, 1994, 1996;Cerra and Saxena, 2002;Singh, 2002Singh, , 2004aAgarwal and Whalley, 2013). A highly limited attempt, however, has been made to assess the sustainability of CADs in an intertemporal Sustainability of current account deficits in India setting Cashin, 1999, 2002;Singh, 2004b;Holmes et al, 2011).…”
Section: Introductionmentioning
confidence: 97%